The utilization of microbial cell-free DNA next-generation sequencing for the detection of human herpesvirus-8 in a quaternary care center - Rebecca Berger; Jennifer Jacobe; Fernando H. Centeno; Todd Lasco; Mayar Al Mohajer (Therapeutic Advances in Infectious Disease)
Background: Human herpesvirus-8 (HHV8) can present with cutaneous or extracutaneous manifestations. While violaceous skin lesions characterize cutaneous Kaposi sarcoma, extracutaneous HHV8 is challenging to diagnose due to nonspecific symptoms. Objectives: We evaluated the role of microbial cell-free DNA next-generation sequencing (mcfDNA NGS) in diagnosing HHV8-related illness. Design: Retrospective analysis. Methods: Between 2017 and 2024, we reviewed the medical charts of 10 immunosuppressed patients at a quaternary care center who had positive HHV8 mcfDNA NGS results. Results: The clinical and laboratory turnaround times of mcfDNA NGS were 3 and 1 days, respectively (8.5 and 7 days for immunohistochemistry vs 5.5 and 2 days for serum HHV8 polymerase chain reaction). Eight patients received HHV8-related diagnoses, while two had unrelated conditions. Management changed in six patients post-testing due to outpatient specialist referral or adjusting antimicrobials. Conclusion: mcfDNA NGS can aid clinicians in identifying HHV8-related diseases before tissue sampling and adjusting treatment plans in patients with nonspecific disease manifestations.